Analisis Unjuk Kerja Kompresor Sentrifugal Pada Unit Flare Gas Recovery PT. Arun NGL - Teuku Juliadi; Ahmad Syuhada; - Hamdani (Jurnal Teknik Mesin Unsyiah, 2013)
PT. Arun NGL has made various efforts torecover losses of energy and water resources during the production process. One of the main focuses for energy conservation is flare gas recovery unit. The flare gas recovery system proposed is skid-mounted type. The primary equipments consists of two compressors that compress the gas from the flare header gas upstream liquid seal drum. The gas is then cooled for reuse in the fuel gas system. The flare gas compressor often experience surge problem due to compressor operating at low flow so that the pressure decreased dramatically while compressor head system stays at high pressure. The compressor playsan important role in generating high-pressure fuel gas. If the compressor is not able to produce enough pressure as required, the production of fuel gas will be disrupted.This analisis focused on the calculation the compressor performance, head, capacity efficiency, and compressor power. Based on the analisys, it is obtained that the flow capacity is 3500 m3/hr, head compressor is 5700 kJ/kg, and the compressor power is 9000 kW. The results show that the operating condition is still whitin the surge limitation.